Revisiting the impact of consumption growth and inequality on poverty in Indonesia during decentralisation - Miranti, R.; Duncan, Alan; Cassells, R. (Routledge, 2014)
This paper analyses the consumption growth elasticity and inequality elasticity of poverty in Indonesia with a particular focus on the decentralisation period. Using provincial panel data, the paper finds that there were more pronounced effects of income inequality on regional poverty rates during later development periods up to decentralisation in Indonesia post-2002. This indicates that the pro-poor impact of economic growth using mean consumption per capita as a proxy of economic growth during decentralisation (a reduction of around 5.7 percentage points in the headcount poverty rate) has been offset to a greater extent by rising income inequality (up from 0.329 in 2002 to 0.380 in 2010) and by the stronger negative impact of inequality on regional poverty rates. In combination, the stronger negative impact of rising inequality has contributed to an increase of around 1.9 percentage points in the headcount poverty rate.